Revenue-Sharing Contract Design for Construction Onsite Equipment Sharing - Liu, Zhi; Wang, Hongwei; Xie, Yong (Frontiers in Built Environment, 2022)
Equipment sharing between contractors can relieve equipment shortages and enhance construction productivity. Previous studies focused on how to allocate cooperative gains of resource sharing among contractors, and yet how to ensure the owner and contractors form a coalition that contributes to maximizing resource-sharing gains still needs to be studied. This article examines the contract design problem of motivating the contractors and owner to willingly cooperate to increase the amount of shared equipment to an optimal level to maximize the project’s overall gain through equipment sharing. First, two trilateral equipment-sharing game models including a critical contractor, a noncritical contractor and the owner are developed, which represent contractors' different leadership positions in equipment sharing. Then, a set of revenue-sharing contracts are devised to compensate the contractors’ equipment-sharing cost and the owner’s extra duration reward cost by reassigning the consequently increased operation income. Eventually, a numerical study demonstrates that the proposed contracts can prompt members to make decisions according to an optimal solution to maximize the overall gains of equipment sharing, and each member’ gain and the construction duration compression are improved. This paper contributes to onsite resource management by introducing a revenue-sharing contract to fairly compensate construction members’ equipment-sharing cost to achieve optimal cooperative gains.